Comparing pre-service teachers’ problem-solving skills in relation to their metacognition and reading comprehension - Azizul Ghofar Candra Wicaksono; Ipah Budi Minarti; Atip Nurwahyunani (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Problem solving has been identified as a critical skill for individuals to adapt to society and is particularly beneficial for educators, especially pre-service teachers. However, this process is complex and is influenced by other predictors, such as metacognition and reading comprehension, which remain underexplored. This study aims to evaluate pre-service teachers’ problem-solving skills and compare them based on their levels of metacognition and reading comprehension. A total of 133 pre-service teachers were included in this study. They completed a self-developed problem-solving test that presented problems related to the use of technology and artificial intelligence in teaching and learning processes. Additional adapted instruments were used, including a reading comprehension test with seven items and a metacognitive questionnaire with eleven items. The participants were then clustered into three groups: the first group represented individuals with high reading comprehension and moderate metacognition; the second group, those with high metacognition and moderate reading comprehension; and the third group, those with moderate levels of both reading comprehension and metacognition. The collected data were analyzed using analysis of variance (ANOVA). The result revealed no significant differences in pre-service teachers’ problem-solving skills (F(130) = 1.023, p = .363). This finding may indicate that once a minimum level of metacognition and reading comprehension is reached, additional gains may not lead to significantly higher problem-solving performance. However, the results should be interpreted cautiously, considering the study’s limitations and the potential presence of a metacognitive ceiling effect.